Analisis Penentuan Harga Jual Dalam Meningkatkan Volume Penjualan Pada Statice_Id Di Kota Surabaya - Hana Citra Kusuma Dewi; Nur Aini Anisa (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to determine the determination of the selling price in increasing sales volume at Statice_Id in the city of Surabaya. This type of research uses qualitative research. Data collection techniques used are interviews and observation. This research uses primary and secondary data. The results of this study indicate that, the determination of the selling price carried out by Statice_Id must calculate the company's expenses. Includes tools and materials for making bouquets, employee salaries, building rental costs, electricity costs, promotional costs and other facilities and infrastructure. Determining the selling price makes Statice_Id always prioritize bouquet quality so that it can increase sales volume.